Successful Implementation of a Medical Student Postpartum Follow-up Phone Call Project - Cynthia Abraham (Association of American Medical Colleges, 2021)
Introduction The American College of Obstetricians and Gynecologists recommends prompt postpartum follow-up. However, 40% of women do not attend postpartum visits. These rates are lower in populations with limited resources. In response, the Department of Obstetrics, Gynecology, and Reproductive Science in the Mount Sinai Health System created a postpartum follow-up phone call project that utilized medical students and was conducted at three health system hospitals from April 6 to May 30, 2020. Methods The number of patients contacted by medical students within 72 hours of hospital discharge was recorded. Students at two of the three sites also recorded the number of patients who needed (1) urgent evaluation and subsequent hospital readmission, (2) medications prescribed, and (3) referral for social work services. Students completed questionnaires at the project beginning and end regarding confidence in rendering of postpartum care. Confidence level was based on a 5-point Likert scale (1 = not confident at all, 5 = very confident). Results Nine students participated. Overall, confidence on providing postpartum care significantly increased from 2.2 to 3.7 (p < .001). Three hundred eighty-seven patients were contacted. Four patients were advised to return to the hospital emergently; two were readmitted. Forty-seven patients needed medication prescribed. Two patients were referred for social work services. Discussion Our medical student-driven postpartum follow-up phone call project was associated with a high number of patients called and management of significant postpartum issues. Students' confidence in managing postpartum issues was significantly higher after versus before project participation.